An Analysis How Customers Ratings and Reviews Impact Prices of Electronics on Lazada - Izzudin, Rafi; Nugroho, Aryo; Prakoso, Muhammad Wisnu; Kirana, Viona Chandra; Nur, Putri Annisa (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the influence of customer ratings and reviews on the prices of e-commerce products listed on Lazada, a leading e-commerce platform. Using a quantitative research design, data from 99 product listings were analyzed using linear regression to explore the relationships between price, total reviews, and average rating. Contrary to initial hypotheses, the results did not reveal a significant predictive power of customer ratings or number of reviews on product prices, highlighting the complexity of online pricing dynamics. The findings suggest that other factors—such as brand reputation, product features, and marketing strategies—play a more substantial role in determining prices. These insights recommend a multifaceted approach to pricing strategies in e-commerce, moving beyond customer feedback metrics to optimize profitability and customer satisfaction. Future research could incorporate additional variables and advanced modeling techniques to deepen the understanding of pricing mechanisms in digital marketplaces.